2018
DOI: 10.1371/journal.pone.0196810
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-based microfluidic analysis and screening of single plant cells

Abstract: Droplet-based microfluidics has been used to facilitate high-throughput analysis of individual prokaryote and mammalian cells. However, there is a scarcity of similar workflows applicable to rapid phenotyping of plant systems where phenotyping analyses typically are time-consuming and low-throughput. We report on-chip encapsulation and analysis of protoplasts isolated from the emergent plant model Marchantia polymorpha at processing rates of >100,000 cells per hour. We use our microfluidic system to quantify t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Yu et al also employed a T-junction in a PDMS-glass device to generate water-in-oil droplets. 185 Here, yellow fluorescent protein (YFP)-modified M. polymorpha protoplasts (plant cells without a cell wall) were encapsulated. The autofluorescence of chlorophyll or the YFP reporter protein was quantified using a confocal microscope with a throughput of 115 200 individual cells per hour.…”
Section: Microfluidicsmentioning
confidence: 99%
“…Yu et al also employed a T-junction in a PDMS-glass device to generate water-in-oil droplets. 185 Here, yellow fluorescent protein (YFP)-modified M. polymorpha protoplasts (plant cells without a cell wall) were encapsulated. The autofluorescence of chlorophyll or the YFP reporter protein was quantified using a confocal microscope with a throughput of 115 200 individual cells per hour.…”
Section: Microfluidicsmentioning
confidence: 99%
“…This application of DMF technology on plant cells analysis can open the opportunity for on-chip fluorescence-based selection of individual plant cells that can be used in targeted regeneration. Combining DMF technology with RNA libraries and gene editing tools like CRISPR-cas9 endonuclease can also improve the academic and industrial research in plant biotechnology [116].…”
Section: Droplet-based Microfluidics For Cellomicsmentioning
confidence: 99%
“…Microfabricated fluorescence-activated cell sorter (µFACS) systems with inline droplet generators offer similar advantages as FACS; however, they eliminate the need for expensive equipment and minimize the probability of channel clogging. One recent example of employing droplet microfluidics for cell sorting has been shown by Yu et al for plant protoplasts, as shown in Figure 1B [21]. Protoplast fluorescence was detected on-chip by coupling a laser-based optical detection setup with electrodes generating a dielectric force dependent on fluorescent readout.…”
Section: Cell-based Protein Synthesis—a Ménage à Trois Of Dropletsmentioning
confidence: 99%
“…Overall, microfluidics proves to be an important tool for synthetic biologists in manipulating cellular systems. The devices offer great advantages such as automated feedback control [18,19], sorting of engineered cells based on protein yield [21,22,25], and on-line detection of cell growth [25,26]. Digital microfluidic devices additionally allow for novel fluid handling operations and process automation.…”
Section: Cell-based Protein Synthesis—a Ménage à Trois Of Dropletsmentioning
confidence: 99%
See 1 more Smart Citation